The Impact of Work Stress and Communication on Lecturer Performance: Mediating Role of Job Satisfaction - Astutik, Yuli; Kartika, Chandra; Wibowo, Nugroho Mardi (JURNAL AL-TANZIM, 2025)
This study aims to examine the impact of work stress, communication, and workability on lecturer performance in Islamic higher education institutions, with job satisfaction as a mediator, and to identify the reciprocal relationship between these factors to improve lecturer performance. This study uses a quantitative design with a correlational approach. Data were collected through a survey involving 100 lecturers, who were selected using a purposive sampling technique. Data analysis was conducted using multiple regression analysis via SmartPLS software. The study’s findings indicate that work stress does not have a direct impact on job satisfaction (T-statistic = 0.518), but it does negatively affect lecturer performance (T-statistic = 4.573). Communication is proven to have a significant effect on job satisfaction (T-statistic = 3.172) and lecturer performance (T-statistic = 2.203). Workability also has a positive impact on job satisfaction (T-statistic = 2.210) and lecturer performance (T-statistic = 3.511). Job satisfaction shows a positive influence on lecturer performance (T-statistic = 3.811). This study highlights the importance of educational institutions in managing work stress, enhancing communication between lecturers, and providing training that can improve lecturers’ work ability and job satisfaction as a strategy to enhance their performance.